Recent amendments to the Endangered Species Act and an uncertain future for species at risk: a case study of Ontario's Niagara Region - Allegra Bethlenfalvy; Andrea Olive (Canadian Science Publishing, 2021)
The biodiversity crisis is a pressing global issue. In Ontario, Canada, species at risk are protected under the Endangered Species Act (2007). The current government amended that legislation through the More Homes, More Choice Act (2019), leaving species at risk with an uncertain future. This paper uses the Niagara Region as a case study and relies on interviews and data collection about listed species to illuminate the possible implications for the new amendments. The results indicate a total of 71 species at risk that exist in the Region, with as many as 37 species that could be delisted and stripped of protection under the recent changes. There is also concern around the prioritization of the economics over science in the amendments. While uncertainty surrounding the implementation of the amendments to the Ontario Endangered Species Act exists, there is agreement that species at risk should be protected.